Acute Pancreatitis in Patient with Malignant Obstructive Jaundice Following Percutaneous Trans Hepatic Biliary Drainage: A Case Report - Amirhosein Ghafouri Asbagh; Zahra Mohammadi Yushanluee; Arash Khameneh Bagheri; Mehran Malekshoar; Payam Bafandeh Tiz; Javad Jalili (Babol University of Medical Sciences, 2025)
Background: Percutaneous Trans hepatic biliary drainage (PTBD) is a successful palliative treatment for malignant obstructive jaundice. Despite the past that PTBD complications occur more frequently. Currently, with the help of an ultrasound guide, these side effects and possibility of adjacent organ damages have decreased interestingly. One of the rare complications of this procedure is acute pancreatitis. Case Presentation: We discuss an uncommon case of acute pancreatitis following PTBD in an elderly woman who presented to the hospital with jaundice and anorexia. Conservative therapy without decatheterization was the treatment of choice in our patient. Eventually after receiving conservative therapy for her pancreatitis, she was discharged from the hospital in good general condition and she has not experienced any episodes of abdominal pain again. Conclusion: Acute pancreatitis is one of the causes of sepsis during PTBD catheterization. Early management of this complication after PTBD can decrease morbidity and mortality of the patients.